Optimization of Discharge Plasma Reactor for Dry Reforming of Methane using Response Surface Methodology - Nabil Majd Alawi; Hassan H. Al-Mohammedawi; Firas Khaleel AL-Zuhairi; Hoang Minh Nguyen; Jamal M. Ali (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
This research provides a study of the dry reforming of methane (DRM), which converts two main greenhouses gases (CO2 and CH4) to synthesis gas (H2 and CO) by a Dielectric Barrier Discharge (DBD) plasma reactor at atmospheric pressure. The Box-Behnken Design (BBD) method based on the Response Surface Methodology (RSM) was applied to determine the optimum experimental conditions on the plasma stability and the synthesis gas production. The synergistic effects of input power (P), CO2/CH4 ratio (R), and flow rate (FR) on the CO2, CH4 conversions, H2, CO yields, and the syngas ratio of H2 to CO were studied. With the desirability value of 0.97, the optimum values of 10.05 W (P), 1.03 (R), and 1.58 L.min−1 FR were identified with CO2 conversion of 48.56% and CH4 conversion of 86.67%; H2 and CO yields of 45.87% and 39.43% respectively; and syngas ratio of H2 to CO of 0.88. The study shows that both P and FR have a major significant effect on the reactant conversions and syngas ratio, followed by R. Meanwhile, the value of R has a significant impact on the H2, CO yields followed P and FR. In contrast, the synergistic effects between P-R, P-FR, and R-FR had a weak significant on the CO2 and CH4 conversions, H2 and CO yields, and H2 to CO ratio respectively. The quadratic term coefficients of P, R, and FR had a remarkable effect on all responses. Thus, the synergistic effect of the most important parameters improves the process efficiency. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).